Rekonstruksi Kepemimpinan Pendidikan Islam Kepala Madrasah Berbasis Nilai-Nilai Islam: Pengembangan Tauhidic Integrative Leadership Model (TILM) di MTsN 6 Kediri - ABAS SHOFWAN; Abd. Aziz; Nur Efendi (CV. Gerasi Insan Nusantara, 2026)
This study aims to analyze the madrasa principal’s understanding of Islamic values, examine their implementation in leadership practices, and reconstruct an Islamic educational leadership model based on these values at MTsN 6 Kediri. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving the principal, teachers, and educational staff. The findings reveal that the principal of MTsN 6 Kediri demonstrates a strong understanding of Islamic values such as trustworthiness (amanah), role modeling, deliberation (musyawarah), and responsibility, which are internalized in leadership practices. These values are reflected in transparent institutional management, productive human resource development, and the establishment of a conducive and familial organizational culture. These conditions are supported by an energetic leadership style, a harmonious school environment, adequate facilities, and strong student achievements. Furthermore, this study reconstructs an Islamic educational leadership model in the form of the Tauhidic Integrative Leadership Model (TILM), emphasizing the integration of spiritual (tauhid), moral, and practical leadership dimensions. The model highlights that effective Islamic educational leadership lies in the holistic integration of values, practices, and institutional context. This study contributes theoretically to the development of value-based Islamic educational leadership studies and practically to strengthening contextual, applicable, and competitive madrasa leadership models.